Kріоконсервування сперматозоїдів людини з полівінілпіролідоном за олігоастенотератозооспермії - Hapon, Hanna; Pavlovich, Olena (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2020)

(untitled)
Probl Cryobiol Cryomed 2020; 30(3): 296